Identification of Reservoir Distribution Using Extended Elastic Impedance (EEI) Inversion in the "Z" Field of the Kutai Basin - Zikra Miftahul Haq; Eki Komara; Wien Lestari (Journal of Earth Energy Engineering, 2023)
This research was conducted using EEI inversion on seismic data in Z Field, Kutai Basin. The EEI inversion is effectively used to determine the reservoir distribution by eliminating the angle limit on the elastic impedance to the Chi angle so that it can be correlated with petrophysical parameters that are sensitive to lithology and fluids. The data used in this study are well data, checkshots, horizons, and partial-stack angle gather 3D seismic data. The data obtained is processed to obtain the target zone first based on log interpretation. Based on data processing, the target zone is obtained at 1513 m to 1531 m. Sensitivity analysis was conducted to determine the sensitive parameters, which can separate the lithology of the formation. In the sensitivity analysis, the most sensitive log to separate lithology is the Vp/VS log, which can separate sandstone, shale, and coal. Furthermore, the EEI inversion analysis was carried out to obtain the most suiTable model for the inversion, the Based Hard Constraint model was obtained with a correlation reaching 0.997 and an error value of 0.078. Based on the EEI inversion, the target zone in the Z-field at a depth of 1258 ms - 1269 ms with a sandstone reservoir in the EEI range of 6000 (m/s)(g/cc) - 7500 (m/s)(g/cc) which spreads from northeast to south. The distribution of the sandstone reservoir is surrounded by coal with a range of EEI 7500 (m/s)(g/cc) - 12000 (m/s)(g/cc), and also the distribution of shale in the EEI range of 7500(m/s)( g/cc) - 9200(m/s)(g/cc).